INTEGRATION OF OUTING CLASS-BASED ECOMEDIA PHOTOVOICE IN CLIMATE CHANGE EDUCATION TO IMPROVE ENVIRONMENTAL LITERACY AMONG ELEMENTARY SCHOOL STUDENTS - Ratna Anggreani; Ganes Gunansyah; Ari Metalin Ika Puspita; Neni Mariana (Universitas Majalengka, 2025)
Objective this research aims to develop photovoice media based on outing class in the context of Climate Change Education (CCE) to foster environmental awareness and intelligence among elementary school students.Method: The approach used is research and development (R&D) with the 4D model, which includes the stages of define, design, develop, and disseminate.Data were collected through expert validation, practicality trials by teachers and students, and effectiveness measurement through pretests and posttests.Results: The expert validation results indicate that the photovoice media has a very high level of validity.Field trials show that this media is very practical and easy to use.The effectiveness of learning has increased, as evidenced by the improvement in students' grades and attitudes towards the environment.Novelty: The integration of photovoice and outing class in the context of CCE provides a visual-contextual approach that strengthens the learning experience based on the real environment.